100 keV H+ ion irradiation of as‐deposited Al‐doped ZnO thin films: An interest in tailoring surface morphology for sensor applications. (31st May 2018) - Sahoo, Susanta Kumar; Mangal, Sutanu; Mishra, D.K.; Singh, Udai P.; Kumar, Pravin
Abstract : We report the influence of 100 keV H + ion beam irradiation on the surface morphology, crystalline structure, and transport properties of as‐deposited Al‐doped ZnO (Al:ZnO) thin films. The films were deposited on silicon (Si) substrate by using DC sputtering technique. The ion irradiation was carried out at various fluences ranging from 1.0 × 10 12 to 3.0 × 10 14  ions/cm 2 . The virgin and ion‐irradiated films were characterized by X‐ray diffraction, Raman spectroscopy, atomic force microscopy, and Hall probe measurements. Using X‐ray diffraction spectra, 5 points Williamson‐Hall plots were drawn to deduce the crystallite site and strain in Al:ZnO films. The analysis of the measurements shows that the films are almost radiation resistant in the structural deformation under chosen irradiation conditions. With beam irradiation, the transport properties of the films are also preserved (do not vary orders of magnitude). However, the surface roughness and the crystallite size, which are crucial parameters of the ZnO film as a gas sensor, are at variation with the ion fluence. As ion fluence increases, the root‐mean‐square surface roughness oscillates and the surface undergoes for smoothening with irradiation at chosen highest fluence. The crystallite size decreases initially, increases for intermediate fluences, and drops almost to the value of the pristine film at highest fluence. In the paper, these interesting experimental results are discussed in correlations with ion‐matter interactions especially energy losses by the ion beam in the material.